Cellular distribution of human leucocyte adhesion molecule ICAM-3. Issue 2 (February 1994) - Cordell, J L; Pulford, K; Turley, H; Jones, M; Micklem, K; Doussis, I A; Tyler, X; Mayne, K; Gatter, K C; Mason, D Y
Abstract : AIMS--To describe the distribution of the recently cloned human leucocyte adhesion molecule ICAM-3 in normal and neoplastic tissues and cell lines. METHODS--A panel of four monoclonal antibodies to ICAM-3 were used to stain cell lines and sections of human lymphoid tissues using the alkaline phosphatase-anti-alkaline phosphatase immunocytochemical method (APAAP). RESULTS--In peripheral blood ICAM-3 was detected on monocytes, granulocytes, and most lymphocytes. In sections of human lymphoid tissue the antigen was also found on most lymphocytes, but many of the proliferating B cells found in the germinal centres of secondary lymphoid follicles were ICAM-3 negative. ICAM-3 was also found on neoplastic white cells (in chronic lymphocytic leukaemia, hairy cell leukaemia, acute and chronic myeloid leukaemia, and multiple myeloma) with the exception of Reed-Sternberg cells in Hodgkin's disease, many of which were negative. ICAM-3 was consistently absent from cells and tissues of non-haemopoietic origin. Endothelium (which expresses ICAM-1) was negative for ICAM-3, with the exception of vessels in some neoplastic lymphoid samples which showed variable staining for ICAM-3. CONCLUSIONS--These findings suggest that ICAM-3 is essentially restricted to the haemopoietic system and is reciprocal in its expression to ICAM-1, in that it is present on resting cells and its level falls as a result of cell activation.